Association between C-reactive protein-triglyceride glucose index and abnormal BMD in middle-aged and elderly patients with type 2 diabetes mellitus: a cross-sectional study - Zhang, Yuan; Jing, Yali (Frontiers in Medicine, 2025)
Background and aimsBone loss is an irreversible physiological change occurring with age. Type 2 diabetes mellitus (T2DM) is associated with poor bone health, and insulin resistance (IR) and inflammation are common pathologic mechanisms in T2DM and osteopenia/osteoporosis (OP). C-reactive protein-triglyceride glucose index (CTI), a novel marker of IR and inflammation, has been Investigated in various diseases. However, its potential association with the incidence of T2DM combined osteopenia/OP in T2DM remains unclear. This study aimed to investigate the association between the CTI and osteopenia/OP in middle-aged and elderly patients with T2DM.MethodsThis retrospective cross-sectional study analyzed 847 middle-aged and elderly patients with T2DM. The CTI was calculated as follows: 0.412 × Ln [CRP (mg/L)]+Ln [TG (mg/dl) × FPG (mg/dl))/2. Spearman correlation analysis was employed to explore the connection among CTI with bone metabolic parameters in T2DM. Further, CTI was included in the logistic regression model as a continuous and categorical variable, respectively, to assess the association between this index and osteopenia/OP in T2DM. Additionally, the operating Characteristic (ROC) curve analysis was adopted to examine the predictive efficacy of the CTI for osteopenia/OP in T2DM.ResultsThis study found that the CTI level was significant higher in osteopenia/OP patients than normal subjects with T2DM (9.179 ± 0.500 vs. 9.684 ± 0.514, p < 0.001). Participants stratified by CTI quartiles showed a progressively increased prevalence of osteopenia/OP with higher CTI levels (22.6%−77.7%, p for trend < 0.001). In Spearman correlation analysis, a remarkably negative correlation was observed between CTI and bone mineral density (BMD) measures in middle-aged and elderly patients with T2DM. When analyzed CTI as continuous variable, after adjustment for the impact of various covariates, there was a significant relationship between CTI and the risk of osteopenia/OP (OR 7.277, 95% CI: 4.602–11.507; p < 0.001). When categorized CTI into quartiles, it still showed a statistically significant association with osteopenia/OP. The area under the ROC curve (AUC) showed a modest standalone predictive ability of 0.758 (95% CI: 0.7254–0.7897; specificity = 69.3%; sensitivity = 71.2%).ConclusionA high CTI is associated with an increased risk of osteopenia/OP in middle-aged and elderly patients with T2DM. Incorporation of routine CTI monitoring into clinical practice may facilitate early detection of high-risk individuals, promote timely intervention, and reduce the burden of T2DM combined with bone metabolic disease.